Ultrasonic elastography-guided pleural biopsy for the diagnosis of pleural effusion: a multicenter prospective study of diagnostic test performance - Deng, Mingming; Ye, Xianwei; Ma, Jiangwei; Xia, Yang; Zhang, Qin; Jiang, Bin; Wu, Jie; Wen, Qing; Zheng, Yujin; Yin, Yan; Tong, Run; Zhou, Guowu; et al. (Annals of the American Thoracic Society, 2023)
Rationale: The diagnostic yield of traditional ultrasound-guided pleural biopsy remains unsatisfactory, particularly when the pleural thickness is ⩽5 mm and/or no pleural nodules are detected. Pleural ultrasound elastography (UE) has a better diagnostic yield than traditional ultrasound for malignant pleural effusion (MPE). However, studies on UE-guided pleural biopsies are lacking. Objectives: To evaluate the feasibility and safety of UE-guided pleural biopsy. Methods: In this multicenter prospective single-arm trial, patients with pleural effusion whose pleural thickness was ⩽5 mm with no pleural nodules were enrolled between July 2019 and August 2021. The diagnostic yield of UE-guided pleural biopsy for pleural effusion and its sensitivity for detecting MPE were evaluated. Results: Ninety-eight patients (mean age, 62.4 ± 13.2 yr; 65 men) were prospectively enrolled. The diagnostic yield of UE-guided pleural biopsy for making any diagnosis was 92.9% (91/98), and its sensitivity for MPE was 88.7% (55/62). In addition, its sensitivity for pleural tuberculosis was 69.6% (16/23). The rate of postoperative chest pain was acceptable, and there was no pneumothorax. Conclusions: UE-guided pleural biopsy is a novel technique for diagnosing MPE with good diagnostic yield and sensitivity.